Comparison of computer tomographic volumetry versus nuclear split renal function to determine residual renal function after living kidney donation - Patankar, K.; Low, R.; Blakeway, David; Ferrari, P. (2014)
Background: Living-donor kidney transplantation is an established practice. Traditionally a combination of renal scintigram and computed tomography (CT) is used to select the kidney that is to be harvested in each donor. Purpose: To evaluate the ability of split renal volume (SRV) calculated from volumetric examination of CT images compared to nuclear split renal function (nSRF) derived from gamma camera scintigram to predict donor residual single kidney function after donor nephrectomy. Material and Methods: This pilot study comprised a retrospective analysis of CT images and renal scintigrams from 12 subsequent live kidney donors who had at least 12 months post-donation renal function follow-up. Results: nSRF derived from the renal scintigram, expressed as the right kidney's function in percent of the total, was 50.2±3.3 (range, 44.1-54.0%) and SRV estimated following analysis of CT imaging was 49.0±2.9 (range, 46.4-52.3%). Although the correlation between nSRF and SRV was moderate (R=0.46), there was 92% agreement on the dominant kidney if a difference of <2% in nSRF versus SRV was considered. Post-donation glomerular filtration rate (GFR) by CKDEPI formula was 92±10 mL/min/1.73m2 at 1 year and the correlation between estimated GFR (eGFR) at 1 year and extrapolated single kidney eGFR adjusted by nSRF (R2=0.69, P=0.0007) or SRV (R2=0.74, P=0.0003) was similar. Conclusion: Calculation of SRV from pre-donation CT examination is a valid method to estimate nSRF with good concordance with nSRF determined by renal scintigram and could replace the latter in the assessment of potential kidney donors. © The Foundation Acta Radiologica 2013.